2023
DOI: 10.4274/dir.2023.232299
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-associated liver morphological changes in hepatic metastases (CALMCHeM)

Abstract: PURPOSE To review imaging findings in chemotherapy-associated liver morphological changes in hepatic metastases (CALMCHeM) on computed tomography (CT)/magnetic resonance imaging (MRI) and its association with tumor burden. METHODS We performed a retrospective chart review to identify patients with hepatic metastases who received chemotherapy and subsequent follow-up imaging where CT or MRI showed morphological changes in the liver. The morphological changes searched for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Systemic chemotherapy, the first line of treatment for metastatic cancer, fails to target metastatic cancer cells; has other serious side effects such as off-target accumulation, toxicity, and rapid renal and hepatic clearance; and has the potential to induce metastasis. 2,3 It has been reported that over 90% of failures in chemotherapy occur during the invasion and metastasis of cancers. 4 Recently, advanced treatment options such as immunotherapy, epigenome-modifying agents, and combination therapy have reduced toxicity in metastatic cancer patients but have limited efficacy in inhibiting tumor metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic chemotherapy, the first line of treatment for metastatic cancer, fails to target metastatic cancer cells; has other serious side effects such as off-target accumulation, toxicity, and rapid renal and hepatic clearance; and has the potential to induce metastasis. 2,3 It has been reported that over 90% of failures in chemotherapy occur during the invasion and metastasis of cancers. 4 Recently, advanced treatment options such as immunotherapy, epigenome-modifying agents, and combination therapy have reduced toxicity in metastatic cancer patients but have limited efficacy in inhibiting tumor metastasis.…”
Section: Introductionmentioning
confidence: 99%